(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
A Deadbeat current controller for an LC coupling hybrid active power filter is proposed, which can track with the reference compensation current with low steady- state error and fast dynamic response. Moreover, it can lead Hybrid Active power Filter to be operating at a fixed switching frequency with low output current ripples, thus reducing the size of the filtering circuit. The stability issue and parameter design of the proposed deadbeat current controller are analyzed and discussed. Finally, the compensating performance of the deadbeat current controller for the Hybrid Active Power Filter (LC-HAPF) is verified by simulation compared with the conventional hysteresis bandwidth modulation control, the proportional-integral (PI) control, and the proportional multi-resonant control for the LC-HAPF, which shows its effectiveness and superior compensating performances.